Genetic Diversity and Phylogenetic Relationships of Coevolving Symbiont-Harboring Insect Trypanosomatids, and Their Neotropical Dispersal by Invader African Blowflies (Calliphoridae) - Borghesan, Tarcilla C.; Campaner, Marta; Matsumoto, Tania E.; Espinosa, Omar A.; Razafindranaivo, Victor; Paiva, Fernando; Carranza, Julio C.; Añez, Nestor; Neves, Luis; Teixeira, Marta M. G.; Camargo, Erney P. (Frontiers in Microbiology, 2018)
This study is about the inter- and intraspecific genetic diversity of trypanosomatids of the genus Angomonas, and their association with Calliphoridae (blowflies) in Neotropical and Afrotropical regions. Microscopic examination of 3,900 flies of various families, mostly Calliphoridae, revealed that 31% of them harbored trypanosomatids. Small subunit rRNA (SSU rRNA) barcoding showed that Angomonas predominated (46%) over the other common trypanosomatids of blowflies of genera Herpetomonas and Wallacemonas. Among Angomonas spp., A. deanei was much more common than the two-other species, A. desouzai and A. ambiguus. Phylogenetic analyses based on SSU rRNA, glycosomal glyceraldehyde-3-phosphate dehydrogenase (gGAPDH) and internal transcribed spacer rDNA (ITS rDNA) sequences revealed a marked genetic diversity within A. deanei, which comprised four infraspecific genotypes (Dea1–Dea4), and four corresponding symbiont genotypes (Kcr1–Kcr4). Host and symbiont phylogenies were highly congruent corroborating their co-divergence, consistent with host-symbiont interdependent metabolism and symbiont reduced genomes shaped by a long coevolutionary history. We compared the diversity of Angomonas/symbionts from three genera of blowflies, Lucilia, Chrysomya and Cochliomyia. A. deanei, A. desouzai and A. ambiguus were found in the three genera of blowflies in South America. In Africa, A. deanei and A. ambiguus were identified in Chrysomya. The absence of A. desouzai in Africa and its presence in Neotropical Cochliomyia and Lucilia suggests parasite spillback of A. desouzai into Chrysomya, which was most likely introduced four decades ago from Africa into the Neotropic. The absence of correlation between parasite diversity and geographic and genetic distances, with identical genotypes of A. deanei found in the Neotropic and Afrotropic, is consistent with disjunct distribution due to the recent human-mediated transoceanic dispersal of Angomonas by Chrysomya. This study provides the most comprehensive data gathered so far on the genetic repertoires of a genus of trypanosomatids found in flies from a wide geographical range.